تقدير انبعاث غازات الاحتباس الحراري من بعض محطات معالجة مياه الصرف الصحي في ريف اللاذقية - سلمان, هناء (Latakia University Journal -Engineering Sciences Series, 2018)
تساهم محطات معالجة مياه الصرف الصحي بانبعاث ثلاثة أنواع من غازات الاحتباس الحراري وهي غاز ثاني أكسيد الكربون CO2، وغاز الميثان CH4، وغاز أكسيد النتروز N2O، وبذلت جهود كبيرة لتقدير كمية هذه الغازات ولتضمين تأثيرها عند تقدير كفاءة محطات المعالجة. يهدف هذا البحث إلى تقدير كمية غازات الاحتباس الحراري المنبعثة من ثلاث محطات صغيرة لمعالجة مياه الصرف الصحي في محافظة اللاذقية، وهي محطة معالجة مرج معيربان ومحطة معالجة الحارة، وتعملان بطريقة التهوية المديدة. ومحطة معالجة الرويمية ويتم فيها إزالة مركبات النتروجين والفوسفور بثلاث مراحل لاهوائية، منقوص الأوكسجين، وهوائية. وبينت النتائج أن كمية الانبعاثات الكلية كقيمة مكافئة لغاز ثاني أكسيد الكربون من المصادر المباشرة لعمليات المعالجة، والمصادر غير المباشرة الناتجة عن استهلاك الطاقة الكهربائية، للمحطات الثلاث هي 464.31 kgCO2e/d، 190.64 kgCO2e/d، 199.37 kgCO2e/dللرويمية والحارة ومرج معيربان على التوالي. كما بلغت كمية الانبعاث المكافئة لكل متر مكعب من المياه المعالجة 1.01 kgCO2e/m3 ، 0.35 kgCO2e/m3 و 0.42 kgCO2e/m3 على التوالي لمحطات الرويمية والحارة ومرج معيربان. مما يبين التأثير الكبير لطريقة المعالجة البيولوجية المتبعة في محطة الرويمية على زيادة كمية انبعاث غازات الاحتباس الحراري، كما يتضح تأثير مواصفات المياه المعالجة وظروف التشغيل على الاختلاف بين كمية الانبعاثات بالنسبة لمحطتي الحارة ومرج معيربان. Wastewater treatment plants contribute to the emission of three types of greenhouse gases (GHG) in the atmosphere CO2, CH4 and N2O. Significant efforts have been made to estimate the amount of these gases and to include them in evaluation the efficiency of treatment processes. This research aims to estimate the amount of greenhouse gases emitted from three small wastewater treatment plants in Latakia countryside, Al-Hara and Merj-Muiraban that used extended aeration, and Al-Rouaimia which included nitrogen and phosphor compounds removal in anaerobic – anoxic – aerobic phases. The results showed that the total amount of GHG emissions from direct and indirect sources for these plants is 464.31 kgCO2e/d, 190.64 kgCO2e/d, and 199.37 kgCO2e/d for Al-Rouaimia, Al-Hara and Merj-Muiraban respectively. The amount of the equivalent emissions per cubic meter of treated wastewater was 1.01 kgCO2e/m3, 0.36 kgCO2e/m3, and 0.34 kgCO2e/m3, respectively for Al-Rouaimia, Al-Hara and Merj-Muiraban plants. The results indicate the significant impact of biological wastewater treatment method at the Al-Rouaimia plant in increase of greenhouse gas emissions, however the effect of the wastewater characterization and operating conditions shows the difference between the quantity of emissions for Al-Hara and Merj-Muiraban wastewater treatment plants.